Successful treatment of nail lichen planus with tofacitinib: a case report and review of the literature - Huang, Jundong; Shi, Wei (Frontiers in Medicine, 2023)
Nail lichen planus (NLP) is a chronic inflammatory disease of unknown etiology and has been recognized as a nail potentially critical disorder, which can be severe and rapidly worsen with irreversible scarring. Currently, the treatment options are limited based on disease progression. High-potency topical or intralesional corticosteroids are commonly considered first-line therapeutic options; however, these therapies are unsuitable for all patients with NLP, especially those with extensive lesions. As a potential therapeutic target for inflammatory skin diseases, Janus kinase (JAK) inhibitors can suppress both type-1 and type-2 cytokines, thereby reducing the immune response and resultant inflammation. Recent studies have suggested benefit in cutaneous lichen planus and lichen planopilaris with oral JAK inhibitors. Here, we report a case of severe NLP that exhibited a favorable response to tofacitinib treatment. A 41-year-old woman presented to our clinic with a 2-year history of nail dystrophy of all fingers of both hands. The NLP was finally confirmed by histopathology and the above clinical features. After the informed consent signature, tofacitinib monotherapy, 5 mg twice a day, was then begun, and after 6 months, the appearance of her nails had a significant improvement.